1993
DOI: 10.1007/bf00296654
|View full text |Cite
|
Sign up to set email alerts
|

Insulin enhances the growth of cartilage in organ and tissue cultures of mouse neonatal mandibular condyle

Abstract: Condylar cartilages were cultured in the form of organ cultures on top of collagen sponges in medium containing 2% fetal calf serum and were treated with 3.5-350 nM insulin for 6 days. Doses of 175 nM of insulin caused a marked increase (+96%) in DNA synthesis and in proteoglycan production (+74%), features that manifested themselves structurally by a 60% increase in overall size of the cultured explants. Using a tissue culture system comprised of cartilage progenitor cells, insulin was found to enhance the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 38 publications
1
23
0
1
Order By: Relevance
“…The presence of Glut4 protein in the growing bone plate was also demonstrated in a rat model (38). The current study further supports the notion that MC organ culture can serve as a reliable model for studies concerning hormonal modulations of skeletal growth (14,26,28,29). Using this model, we have now shown that both insulin and IGF-I stimulate chondrocyte proliferation resulting in an overall increase in the growth of the MC.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The presence of Glut4 protein in the growing bone plate was also demonstrated in a rat model (38). The current study further supports the notion that MC organ culture can serve as a reliable model for studies concerning hormonal modulations of skeletal growth (14,26,28,29). Using this model, we have now shown that both insulin and IGF-I stimulate chondrocyte proliferation resulting in an overall increase in the growth of the MC.…”
Section: Discussionsupporting
confidence: 84%
“…MC organ cultures were prepared as previously described (14,29). Briefly, MC were dissected from 5-to 6-day-old ICR mice and thoroughly washed in cold Hank's buffer.…”
Section: Organ Culturementioning
confidence: 99%
“…It has been suggested that leptin [28] and IGF-1 [8] might contribute to BA advancement in obesity, although recent work by Sopher et al [6] showed no association between these parameters and BA advancement. Future studies in larger cohorts should include these parameters to clarify the role these factors play in this matter.…”
Section: Discussionmentioning
confidence: 98%
“…Insulin is structurally analogous to IGF-1 (insulin-like growth factor 1), which binds to the IGF-1 receptor, and thus elicits similar effects on cartilage (Maor et al, 1993;Schmid, 1995;Gaissmaier et al, 2008). Insulin is structurally analogous to IGF-1 (insulin-like growth factor 1), which binds to the IGF-1 receptor, and thus elicits similar effects on cartilage (Maor et al, 1993;Schmid, 1995;Gaissmaier et al, 2008).…”
Section: Introductionmentioning
confidence: 99%